2021
DOI: 10.52082/jssm.2021.328
|View full text |Cite
|
Sign up to set email alerts
|

Undeclared Doping Substances are Highly Prevalent in Commercial Sports Nutrition Supplements

Abstract: Sports nutrition supplements have previously been reported to contain undeclared doping substances. The use of such supplements can lead to general health risks and may give rise to unintentional doping violations in elite sports. To assess the prevalence of doping substances in a range of high-risk sports nutrition supplements available from Dutch web shops. A total of 66 sports nutrition supplements - identified as potentially high-risk products claiming to modulate hormone regulation, stimulate muscle mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 61 publications
(70 reference statements)
0
52
0
Order By: Relevance
“…This situation seems to be highly prevalent in sports supplements for muscle mass gain, since currently, in the Netherlands, Duiven et al (2021) evaluated a total of 66 products that claimed to modulate hormonal regulation, stimulate muscle mass gain, increase fat loss and/or increase energy, selected from 21 different brands and purchased from 17 online stores. A total of 21 products (32%) contained the presence of at least five different AAS, 1,4-androstenediene-3,17-dione (boldione) being mostly detected in 11 products, followed by 5-androstene-3β,17a-diol, in addition to DHEA, testosterone, and 5-androstenedione.…”
Section: Sports Supplements For Muscle Mass Gainmentioning
confidence: 99%
“…This situation seems to be highly prevalent in sports supplements for muscle mass gain, since currently, in the Netherlands, Duiven et al (2021) evaluated a total of 66 products that claimed to modulate hormonal regulation, stimulate muscle mass gain, increase fat loss and/or increase energy, selected from 21 different brands and purchased from 17 online stores. A total of 21 products (32%) contained the presence of at least five different AAS, 1,4-androstenediene-3,17-dione (boldione) being mostly detected in 11 products, followed by 5-androstene-3β,17a-diol, in addition to DHEA, testosterone, and 5-androstenedione.…”
Section: Sports Supplements For Muscle Mass Gainmentioning
confidence: 99%
“…The reported prevalence reported in the present study can be considered worrying, as pre-workout formulas are associated with side-effects (dizziness and nausea) and adverse events, such as heart rhythm abnormalities [ 46 ]. In addition, a recent study, targeting the Dutch market, reported that pre-workout supplements, readily available in web shops, are ‘at risk’ of containing undeclared doping compounds, mostly anabolic steroids and stimulants [ 47 ]. In this regard, it is alarming that 25% of the pre-workout users in the present study use a pre-workout supplement before every workout.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the present study shows that 65% use the internet and 32% use social media as their primary source of information on dietary supplements. In this regard, it is worrying that 38% of high-risk dietary supplements (e.g., pre-workout) sold online in the Netherlands contain undeclared doping compounds [ 47 ]. On top of that, it is alarming to note that regular gym users have a higher lifetime prevalence rate of AAS use than elite athletes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One definition of dietary supplements was published in a recent consensus statement as “A food, food component, nutrient, or non‐food compound that is purposefully ingested in addition to the habitually consumed diet with the aim of achieving a specific health and/or performance benefit.” 65 Despite ongoing debates about the effectiveness of such supplements, an enormous and competitive market offering an extremely large variety of dietary supplements has developed, which compared with pharmaceuticals, is regulated in a postmarket fashion with products generally not required to undergo rigorous clinical evaluation for safety and efficacy. As comprehensively summarized in a recent review 18 and corroborated in a new study on risks of ADRVs associated with dietary supplements, 66 the issue of contaminated and adulterated supplements containing prohibited substances still exists. Contaminants or adulterants may or may not be explicitly listed on the product label, unconventional or generalized nomenclature may be used to conceal a prohibited ingredient (e.g., proprietary blends), and products themselves can be ambiguously viewed as relatively low risk (e.g., vitamins) to high risk (e.g., “testosterone boosters”).…”
Section: Scenarios Of Potential Suspected And/or Proven Exposure‐caused Aafsmentioning
confidence: 95%